Long-Term Trends in Stroke Survivors Discharged to Care Homes: The South London Stroke Register. Issue 1 (January 2020) - Clery, Amanda; Bhalla, Ajay; Bisquera, Alessandra; Skolarus, Lesli E.; Marshall, Iain; McKevitt, Christopher; Rudd, Anthony; Sackley, Catherine; Martin, Finbarr C.; Manthorpe, Jill; Wolfe, Charles; Wang, Yanzhong
Abstract : Background and Purpose—: Care homes provide care to many stroke survivors, yet little is known about changes in care home use over time. We aim to determine trends in discharge to care homes, to explore the characteristics of stroke survivors over time (1995–2018), and to identify the associations between these characteristics and discharge to care homes poststroke. Methods—: Using data from the South London Stroke Register between 1995 and 2018, we estimated the proportions discharged to care homes and their characteristics over time, assessed by tests for trends. Multivariable logistic regression models were built to assess the associations between their characteristics and discharge destination. Results—: Of 4172 stroke survivors, 484 (12%) were discharged to care homes. This proportion has decreased from 24% in 1995 to 2000 to 5% in 2013 to 2018. The mean age of those discharged to care homes has increased over time, from 73 to 75 ( P <0.001). Among stroke survivors discharged to a care home, the proportion with a prestroke Barthel Index <15 has also increased over time from 7% to 21% ( P =0.027), while the proportion with a 7-day poststroke Barthel Index <15 remains largely unchanged over time (93% in 1995–2000, 90% in 2013–2018). The characteristics most strongly associated with discharge to care homes were (odds ratio [95% CI]) age (1.05 [1.04–1.07] per year), stroke subtype (hemorrhagic; 0.64 [0.43–0.95]), stroke severity (Glasgow Coma Scale score, <13; 1.67 [1.19–2.35]), failed swallow test at admission (1.65 [1.20–2.25]), 7-day poststroke Barthel Index <15 (3.58 [2.20–6.03]), and a longer hospital stay (1.02 [1.02–1.03] per day). Conclusions—: Over >20 years, there has been an 80% reduction in the proportion of stroke survivors discharged to care homes, influenced by changes in the demographics, disability, and stroke care in the underlying stroke population. In those moving to care homes, the level of poststroke disability remains high, requiring continued attention and investment. Abstract : Supplemental Digital Content is available in the text.